Shoulder Girdle Muscles Endurance in Subjects with and without Impingement Syndrome - Afsoun Nodehi-Moghadam; Zahra Rouhbakhsh; Ismaiel Ebrahimi; Mahyar Salavati; Davoud Jafari; Zahra Mohammadi (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: Any minimal alteration in performance and coordination of scapular and glenohumeral muscles has the potential to lead to shoulder joint dysfunction. The impingement syndrome has been reported as is the most common diagnosis of shoulder pain. The purpose of this study was to determine whether endurance deficits could be detected in patients with shoulder impingement. Materials & Methods: By convenient sampling 15 patients with impingement syndrome at average of 45.3 years of age and 15 healthy persons (age 45.8 years) through a case-control design participated in the study. Endurance of glenohumeral and scapulothoracic muscles were tested with a hand held dynamometer. Independent t-test was used to statistically analyze different groups. Results: Compared to non-impaired subjects, those with impingement syndrome demonstrated a significantly lower endurance of external rotation, scaption and scapular abduction and upward rotation movements (P<0.05). In impingement syndrome patients, the external-to-internal rotator muscles endurance ratio was significantly lower than the control group (P<0.05). Conclusion: The result of the study suggests that endurance deficit of rotator cuff and scapular upward rotator muscles may be an important aspect of the impingement syndrome. Shoulder girdle muscles endurance should be considered in evaluation and physical therapy of impingement syndrome patients.